2006
DOI: 10.1111/j.1439-037x.2006.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoyield Analysis of Barley Cultivar Trials in the Canadian Prairies

Abstract: Classification of test sites used for cultivar trials into groups with similar within-group site performance and response (isoyield groups) is an important step towards identification of appropriate cultivars that are best suited for different productivity levels in farm fields. The objective of this study was to determine isoyield environments in the Canadian prairies based on the analysis of cultivar trials consolidated from individual provinces for barley (Hordeum vulgare L.). Yield data for the analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Our classification considered only wheat variability, which is different from the method used by Iglesias et al (), who applied cluster analysis to group Spain into agro‐climatic regions based on temperature and precipitation data. Other agro‐climate classifications have considered yield in combination with topographical or soil characteristics (Yang et al , ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our classification considered only wheat variability, which is different from the method used by Iglesias et al (), who applied cluster analysis to group Spain into agro‐climatic regions based on temperature and precipitation data. Other agro‐climate classifications have considered yield in combination with topographical or soil characteristics (Yang et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Our classification considered only wheat variability, which is different from the method used by Iglesias et al (2000), who applied cluster analysis to group Spain into agro-climatic regions based on temperature and precipitation data. Other agro-climate classifications have considered yield in combination with topographical or soil characteristics (Yang et al, 2006). K-means clustering aims to partition a given dataset into a number of clusters in which each cluster is determined by the degree of similarity and difference between observations.…”
Section: K-means Clusteringmentioning
confidence: 99%
“…Since unpredictable year-to-year weather fl uctuation typical in the Canadian Prairies contributes signifi cantly to yield variation and site instability, Yang et al (2005Yang et al ( , 2006 suggested a normalized procedure to fi lter out much of the random variation among years so that clustering locations would be based on more accurate estimates of location averages. However, it remains largely unknown as to the eff ectiveness of such a normalization as a general procedure because it depends on the level of imbalance in year × location × genotype combinations and on yearly diff erences in location × genotype cell means.…”
Section: Issue 3: How Realistic Is a "Which-won-where" Pattern From Amentioning
confidence: 99%
“…The fi rst data set used for the mixed-eff ect model, involving fi xed genotypic eff ects and random environmental eff ects, was taken from the Canadian Prairies Barley Trials as described in Yang et al (2006). The fi rst data set used for the mixed-eff ect model, involving fi xed genotypic eff ects and random environmental eff ects, was taken from the Canadian Prairies Barley Trials as described in Yang et al (2006).…”
Section: Data Setsmentioning
confidence: 99%
“…Two data sets were used for the COI assessment under the mixed-eff ect model. The fi rst data set used for the mixed-eff ect model, involving fi xed genotypic eff ects and random environmental eff ects, was taken from the Canadian Prairies Barley Trials as described in Yang et al (2006). While these trials included a large number of cultivars and advanced breeding lines, a focus has been on the following six two-row barley cultivars (Helm et al, 2004): three eligible for feed grades-'CDC Dolly', 'Seebe', and 'Xena'-and three others eligible for malting grades-'AC Metcalfe', 'Harrington', and 'Merit'.…”
Section: Data Setsmentioning
confidence: 99%